Molecular interactions of plant oil components with stratum corneum lipids correlate with clinical measures of skin barrier function - Mack Correa, Mary Catherine (BlackWell Publishing Ltd, 2014)
Plant-derived oils consisting of triglycerides and small amounts of free fatty acids (FFAs) are commonly used in skincare regimens. FFAs are known to disrupt skin barrier function. The objective of this study was to mechanistically study the effects of FFAs, triglycerides and their mixtures on skin barrier function. The effects of oleic acid (OA), glyceryl trioleate (GT) and OA/GT mixtures on skin barrier were assessed in vivo through measurement of transepidermal water loss (TEWL) and fluorescein dye penetration before and after a single application. OA's effects on stratum corneum (SC) lipid order in vivo were measured with infrared spectroscopy through application of perdeuterated OA (OA-d(34)). Studies of the interaction of OA and GT with skin lipids included imaging the distribution of OA-d(34) and GT ex vivo with IR microspectroscopy and thermodynamic analysis of mixtures in aqueous monolayers. The oil mixtures increased both TEWL and fluorescein penetration 24 h after a single application in an OA dose-dependent manner, with the highest increase from treatment with pure OA. OA-d(34) penetrated into skin and disordered SC lipids. Furthermore, the ex vivo IR imaging studies showed that OA-d(34) permeated to the dermal/epidermal junction while GT remained in the SC. The monolayer experiments showed preferential interspecies interactions between OA and SC lipids, while the mixing between GT and SC lipids was not thermodynamically preferred. The FFA component of plant oils may disrupt skin barrier function. The affinity between plant oil components and SC lipids likely determines the extent of their penetration and clinically measurable effects on skin barrier functions.